Renoprotective Effect of Thai Patients with Type 2 Diabetes Mellitus Treated with SGLT-2 Inhibitors versus DPP-4 Inhibitors: A Real-World Observational Study - Apichaya Chanawong; Suriyon Uitrakul; Supatcha Incomenoy; Natnicha Poonchuay (Advances in Pharmacological and Pharmaceutical Sciences)
Background. Recently, there is a lack of studies comparing the renoprotective effects of sodium-glucose cotransporter-2 (SGLT-2) inhibitors and dipeptidyl peptidase-4 (DPP-4) inhibitors. This study therefore aimed to investigate the renoprotective effects of SGLT-2 inhibitors and DPP-4 inhibitors on Thai patients with type 2 diabetes mellitus. Methods. Patient medication records of all patients who used those two antidiabetic classes at Fort Wachirawut Hospital were reviewed. Renal function tests, blood glucose levels, and other baseline characteristics were collected. Continuous variables were compared within the group using the Wilcoxon signed-rank test and between groups using the Mann–Whitney U test. Results. There were 388 and 691 patients with SGLT-2 inhibitors and DPP-4 inhibitors, respectively. The mean estimated glomerular filtration rate (eGFR) of the SGLT-2 inhibitor group was significantly lower from baseline at 18 months of treatment, as well as the DPP-4 inhibitor group. However, the trend of eGFR reduction in patients with baseline eGFR <60 mL/min/1.73 m2 was smaller than those with baseline eGFR ≥60 mL/min/1.73 m2. In addition, the fasting blood sugar and haemoglobin A1c levels significantly decreased from baseline in both the groups. Conclusions. Both SGLT-2 inhibitors and DPP-4 inhibitors showed the same trends of eGFR reductions from baseline in Thai patients with type 2 diabetes mellitus. However, SGLT-2 inhibitors should be considered in patients with impaired renal function rather than in all T2DM patients.